(untitled) (The International Research Journal of Management Science, 2025)
Purpose: The purpose of this paper is to explore the determinants of entrepreneurial financial wellbeing in Dang district of western Nepal. Method(s): The causal comparative research design was adopted as the positivist research paradigm to discover objective reality. The paper adopts a survey by questionnaire method to gather data from 412 entrepreneurs through the purposive sampling under non-probability sampling technique. The data was evaluated by using descriptive and inferential statistics. Measurement modeling as well as structural equation modeling (SEM) was used and data analyzed by PLS 4.1.1.2. Finding(s): The study’s findings show that mental budgeting; materialism and self-control have a significantly influenced on financial wellbeing of entrepreneurs but financial literacy haven’t significantly influenced on financial wellbeing of entrepreneurs. Conclusion: This study shows that the entrepreneurs of Dang district are mentally prepared regarding budgeting, focused on materialism and able to self-control. Hence, there is a considerable possibility of financial wellbeing of entrepreneurs, according to the research. Implication(s): This study has significant implications to entrepreneurs, policymakers and financial institutions in Nepal. Originality: This research is original and is not published in other publications.